DEVELOPMENT OF ASSESSMENT PRACTICUM OF PLANT ANATOMY AND PHYSIOLOGY (International Conference on Social and Islamic Studies, 2022)
The research aims to develop a valid, and practice assessment for laboratory of plant anatomy-physiology. The study was development research of Plomp development model. The study consisted of five phases, namely the preliminary investigation phase, design phase, realization or construction phase, test, evaluation, revision phase, and implementation phase. Assessment developed were tested to students of Biology Education Department, State Islamic University (UIN) Alauddin, Makassar. The research results indicated that the assessment developed has met valid with the Gregory content validity coefficient is 1 which means 100% valid . The implementation of the assessment tool is in category 3 which means that most of it is implemented. it can be concluded that the assessment developed is suitable for use in plant anatomy and physiology practicum.